Synthesis and antimicrobial evaluation of some new quinazolin-4(3H)-one derivatives - Fawzy, Naglaa; Ghobashy, Madeha Othman Ibrahim; El-Ziaty, Ahmed Kamel (European Journal of Chemistry, 2012)
The oxazolone derivative 1 was synthesized and converted into a hitherto 3,1-benzoxazin-4-one derivative, 3. A series of quinazolin-4-one derivatives 4a-c and 7-11, as well as quinolinone-3-carboxylic acid derivative, 6, and the amide derivatives, 5a,b, were also synthesized via the 3,1-benzoxazin-4-one derivative. The antimicrobial activity of some of the synthesized compounds was examined against three Gram-positive bacteria (Staphylococcus aureus, Streptococcus mutans and Bacillus subtilis), five Gram-negative bacteria (Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Proteus mirabilis and Acinetobacter baumannii) and one fungi (Candida albicans), using diffusion method. The results showed that compounds 4a, 7, 10 and 11 exhibited significant antibacterial and antifungal activity comparable to standard drugs.